Congenital afibrinogenemia: a case report of a spontaneous hepatic hematoma. Issue 28 (July 2016) - Malaquin, Stephanie; Rebibo, Lionel; Chivot, Cyril; Badoux, Louise; Mahjoub, Yazine; Dupont, Herve
Abstract: Introduction: Afibrinogenemia is a rare coagulation disorder. Clinical features of spontaneous bleeding, bleeding after minor trauma, or after surgery have been described as well as thrombo-embolic complications. In this article, we presented the case of a 19-year old female with congenital afibrinogenemia who was admitted with a spontaneous intrahepatic hematoma. Conclusions: Supportive treatment including transfusion and fibrinogen administration, associated with repeated packing surgeries and selective embolization, were successfully performed.